History and structure of Hymns of the people of God, Vol. 1 - Steuernagel, Marcell Silva (Vox Scripturae - Revista Teológica Internacional, 2016)
This paper offers an introduction to the origins of the Evangelical Church of the Lutheran Confession in Brazil (ECLCB/IECLB), in order to contextualize the history of the publication of Hymns of the People of God (vol. 1), the first volume of this denomination’s official hymnal since 1981. It then examines the hymnal statistically and thematically, presenting a few quantitative conclusions in terms of authorship, time period, and themes, in light of the declared objectives of the committee who worked on the publication of the hymnal.